BIO464: Processes in Ecology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2021)
This course introduces the fundamental concepts of Ecology where the theme is to explain the factors that affect the Distribution and Abundance of Organisms in their natural environment; the functional relationship between Population, Community and Ecosystem with respect to the biotic and abiotic processes and functions within these ecological hierarchies; and the importance of Biodiversity